2019
DOI: 10.14341/probl199844247-51
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of insulin-dependent diabetes mellitus

Abstract: The epidemiology of diabetes mellitus (DM) is a section of diabetology that includes the study of the basic laws of the formation of the epidemiological situation and the epidemiological conditions in relation to this disease, as well as environmental, social and biological factors that determine the dynamics of its main epidemiological characteristics. The end points of the epidemic process are the prevalence of cases of the disease, their frequency and mortality of patients with diabetes. Each of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Распространенность ожирения в мире столь велика, что приобрела характер глобальной эпидемии. Наряду с ростом частоты ожирения отмечается увеличение распространенности и усугубление течения связанных с ним тяжелых соматических заболеваний [сахарный диабет 2 типа (CД2), артериальная гипертония (АГ), ишемическая болезнь сердца (ИБС), онкологические заболевания и другие], снижающих качество жизни и повышающих уровень смертности среди трудоспособного населения [1].…”
Section: Correction Of the Functional State Of The Renal Tubules коррunclassified
“…Распространенность ожирения в мире столь велика, что приобрела характер глобальной эпидемии. Наряду с ростом частоты ожирения отмечается увеличение распространенности и усугубление течения связанных с ним тяжелых соматических заболеваний [сахарный диабет 2 типа (CД2), артериальная гипертония (АГ), ишемическая болезнь сердца (ИБС), онкологические заболевания и другие], снижающих качество жизни и повышающих уровень смертности среди трудоспособного населения [1].…”
Section: Correction Of the Functional State Of The Renal Tubules коррunclassified
“…In particular, 20 HBOT sessions decreased fasting glucose by 21% and ameliorated glucose tolerance by 34%, suggesting that hyperbaric environment influences glucose metabolism, either by improving glucose uptake or glucose oxidation in the postprandial state (Vera‐Cruz et al., 2015). In type 1 diabetes (T1D), a study demonstrated enhanced residual insulin secretion as a result of hyperbaric oxygenation (Dedov, Lukich, Bol'shakova, Gitel, & Dreval, 1987).…”
Section: The Impact Of Hyperbaric Environment On Glucose Homeostasismentioning
confidence: 99%